Fabrication and thermomechanical evaluation in controlled atmospheres of SiC/Si biomorphic compounds - Gamarra-Delgado J.F. (2020)
Biomorphic SiC/Si compounds were fabricated from copaiba wood (Copaifera officinalis, natural wood native to Peru), by reactive infiltration of molten silicon in a porous carbon preform obtained by a controlled pyrolysis process of wood. Structural and microstructural characterization tests by X-ray diffraction and scanning electron microscopy, respectively, revealed, on the one hand, the presence of crystalline phases of SiC, Si and C, and on the other, the typical morphology of this type of material, which it consists of a continuous SiC scaffold with elongated channels in the direction of tree growth and the presence of residual Si and C located mainly in the porosities of the material. The mechanical behavior in uniaxial compression was also studied at a constant compression rate of 0.05 mm/min and as a function of temperature (from ambient to 1400 ºC) and test atmosphere (ambient air, humid air, dry air, Ar, N2 and reducing mixture (95% Ar + 5% H2). The mechanical results were evaluated based on values of maximum stress and modulus of elasticity (stiffness), finding a clear reduction in the values of maximum stress and stiffness of the material when the samples passed of ambient test temperatures at 1400 ºC. On the other hand, mechanical tests in a controlled atmosphere were carried out at a constant temperature of 1100 ºC and the results showed that the mechanical behavior of the studied compounds is slightly influenced by the working atmosphere. Mechanical data found in the various test conditions will be an important support for the definition of the maximum allowable stress (considering the safety factor applied for a particular case) in the industrial application of the materials studied in this work. © 2020, Avestia Publishing. All rights reserved.